Comparison of 3D Double Inversion Recovery (DIR) versus 3D Fluid Attenuated Inversion Recovery (FLAIR) in precise diagnosis of acute optic neuritis. Issue 155 (October 2022) - Murumkar, Vivek; Priyadarshini Baishya, Priyanka; Kulanthaivelu, Karthik; Saini, Jitender; Manjunath, Netravathi; Kumar Gupta, Rakesh
Abstract: Background: The small size, intraorbital fat, perioptic CSF sheath and air-bone interface pose challenges to optic nerve imaging in cases of acute optic neuritis. The study is intended to compare the diagnostic accuracy of 3-dimensional Fluid Attenuation Inversion Recovery (3D FLAIR) and 3-dimensional Double Inversion Recovery (3D DIR) in cases of acute optic neuritis (AON). Methods: Cases of AON with visual evoked potentials (VEP) abnormality were recruited and compared with controls. Imaging protocol incorporated 3D FLAIR and 3D DIR to routine sequences. The optic nerve signal was evaluated for hyperintensity across three segments viz, intraorbital, prechiasmatic, and optic-chiasm segments. The inter-modality agreement, odds ratio, receiver operator characteristics (ROC) curve, Signal intensity ratio (SIR) and interobserver agreement (between two experienced neuroradiologists) was compared between the sequences. Results: Good Intermodality agreement (IMA) was found in the PC segment (ICC: 0.748, p < 0.001) in the Likert scale. In a binary scale of analysis (signal Normal vs abnormal) Kappa was highest for the PC segment (0.525, p < 0.001). The 3D-DIR sequence had an overall higher odds ratio (OR) of detecting abnormality compared to 3D-FLAIR. OR was highest for 3D DIR in the Orbital segment (OR: 3.64, P-value < 0.001) and for FLAIR in the chiasmal segment (OR 2.25, P = 0.007) for predicting optic neuritis. The area under the ROC curve for 3-D DIR was larger across all the segments (0.8 vs 0.623, p < 0.001). The Area under ROC for signal intensity ratio was higher for 3D-DIR(0.844 vs 0.704, p = 0.004) Conclusion: 3D DIR, under its unique contrast-generating scheme, demonstrates a greater diagnostic accuracy and offers confidence in the diagnosis of AON lesions when compared to 3D FLAIR.